2020
DOI: 10.1126/sciadv.aay2103
|View full text |Cite
|
Sign up to set email alerts
|

A statistical inference approach to reconstruct intercellular interactions in cell migration experiments

Abstract: Migration of cells can be characterized by two, prototypical types of motion: individual and collective migration. We propose a statistical-inference approach designed to detect the presence of cell-cell interactions that give rise to collective behaviors in cell-motility experiments. Such inference method has been first successfully tested on synthetic motional data, and then applied to two experiments. In the first experiment, cell migrate in a wound-healing model: when applied to this experiment, the infere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…[20] where the large deviation theory of time-averaged statistics [21] was used to find some stochastic properties of measured trajectories, Ref. [22] where a statistical inference approach designed to find interactions between moving particles was used in experimental data, and Ref. [23,24] where a method based in the information contained in the power spectral density of a single trajectory was proposed (for reviews and other methods see also [25][26][27]).…”
Section: Introductionmentioning
confidence: 99%
“…[20] where the large deviation theory of time-averaged statistics [21] was used to find some stochastic properties of measured trajectories, Ref. [22] where a statistical inference approach designed to find interactions between moving particles was used in experimental data, and Ref. [23,24] where a method based in the information contained in the power spectral density of a single trajectory was proposed (for reviews and other methods see also [25][26][27]).…”
Section: Introductionmentioning
confidence: 99%
“…Using a mathematical model, Agliari et al. explored the hypothesis that ATP release and autocrine signaling during immune cell migration might impact neighboring cells while migrating as a group of single cells ( 140 ). The statistical inference approach revealed that migrating DCs have no instantaneous cell communication via release of small soluble molecules, such as ATP ( 140 ).…”
Section: Discussionmentioning
confidence: 99%
“…explored the hypothesis that ATP release and autocrine signaling during immune cell migration might impact neighboring cells while migrating as a group of single cells ( 140 ). The statistical inference approach revealed that migrating DCs have no instantaneous cell communication via release of small soluble molecules, such as ATP ( 140 ). However, the model only predicts immediate interactions and the release of adenine nucleotides or other small molecules will act with a delay considering the diffusion time and other parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its simplicity, this elementary model leads to very interesting emergent behavior and generates quite natural synthetic trajectories. , Examples can be found in Figure c,d.…”
Section: Methods B: Computational Protocolsmentioning
confidence: 99%